Analisis perlakuan akuntansi sewa berdasarkan PSAK No. 73 pada PT. PLN (Persero) Unit Induk Distribusi Suluttenggo - Malango, Dea Ananda; Saerang, David P. E.; Lambey, Robert (Yayasan Widyantara Nawasena Raharja, 2024)
State-Owned Enterprises (BUMN) must follow changes in the applicable accounting standards policy. This includes the lease accounting policy in accordance with PSAK No. 73. These standards are designed to ensure consistency and transparency in financial reporting. The transition from PSAK No. 30 to PSAK No. 73 will have a significant impact on the accounting treatment of leases and the company's financial statements. This study will analyse the accounting treatment of leases and their impact on State Electricity Company (PT PLN Persero) Unit Induk Distribusi Suluttenggo. This study employs a qualitative research method with a descriptive analysis approach. The data was obtained through interviews with the relevant parties and a thorough examination of the company's financial statements. The results clearly show that the company's accounting treatment of leases is in line with PSAK No. 73. However, there are some areas where the presentation of leases could be improved. The transition has had a positive impact on the company's financial statements, with an increase in total assets and liabilities due to the recognition of lease assets and liabilities on the balance sheet and a decrease in total operating expenses.